Penggunaan Aplikasi Sistem Terdistribusi Pada Sistem Aplikasi Absensi Online Dengan Metode Grounded Research Di Kelurahan Tanjung Pinang - Hetty Rohayani; Rico; Arif Mursidan; Rahmi Handayani (LPPM Universitas Adiwangsa Jambi, 2024)
This study aims to overcome problems and meet the needs of online attendance application users in the Tanjung Pinang Village. Literature study and data collection through observation and interviews are used to analyze the needs and problems faced by users. Solutions for using an effective and efficient online attendance application are found through improvements to the technology infrastructure and data verification system. The results of evaluating the implementation of the solution are upgrading the online attendance application to an attachment manager application so that it shows an increase in speed and accuracy in updating data and the level of user satisfaction. It can be concluded that the use of distributed systems in online attendance applications can meet user needs and overcome problems encountered.